Criminal-law qualification of failure to pay social insurance contributions (Ius Novum, 2019)
This article is a polemic against some views expressed by Krzysztof Ślebzak and Jacek Kosonoga in their paper entitled Liability of a social security contribution payer for calculation, deduction and submission of social security contributions [Odpowiedzialność płatnika składek za obliczanie, potrącanie i przekazywanie składek na ubezpieczenie społeczne], published in Ius Novum No. 3 of 2016. Appreciating the value of the views presented in the above study, the author disputes some of them concerning criminal-law qualification of a conduct consisting in failure to pay social insurance contributions. In the view of the author of this polemic, failing to pay social insurance contributions for an employee does not violate any of the employee rights in the area of social insurance that would be subject to protection by virtue of Article 218 § 1a Criminal Code. However, if the due contributions were deducted from the salary, failure to pay them may constitute the violation of an employee right resulting from employment, i.e. the right to remuneration for work. Only with reference to that part of unpaid contribution, is it possible to commit a crime under Article 218 § 1a Criminal Code. Furthermore, social insurance contributions in the part deducted from the salary of the insured person cannot be misappropriated, because they are neither material things nor a property right provided for in Article 284 § 1 Criminal Code. The author also suggests that a crime consisting in failure to pay social insurance contributions or other forms of social security premiums which are statutorily due to the ZUS Social Insurance Institution should be introduced to the Criminal Code.
Keywords: contributions; social insurance; criminal liability; offence; social insurance contribution payer